The Modulatory Role of Cortisol in the Regulation of Sexual Behavior in Young Males - Rodríguez-Nieto, Geraldine; Sack, Alexander T.; Dewitte, Marieke; Emmerling, Franziska; Schuhmann, Teresa (Frontiers in Behavioral Neuroscience, 2020)
The proneness to be sexually aroused, to perform sexual acts, or to be sexually disinhibited during a particular mood varies across individuals. However, the physiological mechanisms underlying this specific and variable relationship between mood and sex-related processes are poorly understood. We propose that cortisol may act as an important moderator in this as it has shown to influence sexual arousal and to play a neuromodulatory role during emotion regulation. Here, we conducted a functional magnetic resonance imaging study to investigate whether cortisol modulates the neural response during the approach of sexual stimuli in an approach-avoidance task and whether this potential relationship explains the individual differences in sexual inhibition and in mood-related sexual interest and activity. We revealed that cortisol associates to the anteromedial prefrontal cortex activation during the approach towards sexual stimuli. Moreover, this anteromedial prefrontal cortex response was dependent on individual differences in sexual inhibition and the improvements of negative mood as a result of sexual activity. The anteromedial prefrontal cortex is already known to process bottom-up information, reward, and risk estimation. The neuromodulatory role of cortisol within this region during sexual approach may represent a previously unknown yet key element in the regulation of sexual behavior.